Photocatalytic Degradation of 5‐Fluorouracil by Diatomite‐Supported Titanium Dioxide under UV‐A Irradiation. Issue 38 (18th October 2019) - Djediai, Houria; Benrabaa, Rafik; Gombert, Bertrand; N'Guettia, Roland Kossonou
Abstract: The aim of this work is the photocatalytic degradation of 5‐fluorouracil from water with titanium dioxide supported on Algerian diatomite. Different methods and amounts of titanium dioxide (30 and 50% weight) are used to synthesize photo‐catalysts which are characterized (X‐ray powder diffraction (XRD), Scanning electron microscopy (SEM), The specific surface area (BET) and X‐ray fluorescence). The degradation efficiency is enhanced by the increasing of TiO2 amount in diatomite matrix. Under our experimental conditions, diatomite supported commercial TiO2 showed the higher performance for the removal of 5‐fluorouracil. Abstract : The Photocatalytic of 5‐fluorouracil under UV−A irradiation over TiO2 supported on Algerian diatomite are investigated using titanium dioxide from two different precursors. Two methods of preparation with two amounts of titanium dioxide will be used and characterized. A significant effect of TiO2 sources is observed. Proportional relationship between the amount of TiO2 and the activity is established. Anatase structure conduce to best photocatalytic performances.